2023
DOI: 10.1021/jacs.3c06289
|View full text |Cite
|
Sign up to set email alerts
|

Halide Adsorption Enhances Electrochemical Hydrogenolysis of 5-Hydroxymethylfurfural by Suppressing Hydrogenation

Xin Yuan,
Kwanpyung Lee,
J. R. Schmidt
et al.

Abstract: Reductive upgrading of 5-hydroxymethylfurfural (HMF), a biomass-derived platform molecule, to 2,5-dimethylfuran (DMF), a biofuel with an energy density 40% greater than that of ethanol, involves hydrogenolysis of both the aldehyde (CO) and the alcohol (C–OH) groups of HMF. It is known that when hydrogenation of the aldehyde occurs to form 2,5-bis(hydroxy­methyl)furan (BHMF), BHMF cannot be further reduced to DMF. Thus, aldehyde hydrogenation must be suppressed to increase the selectivity for DMF production. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Given that Br – was coadsorbed over Cu, and it was previously reported to enhance HMF hydrogenolysis to DMF, we further conducted catalytic tests using BTA­(NTf 2 ) and HBr as the alternative to BTAB (Figure S23). The catalytic results reveal that Cu–Br – delivers a lower FE for FA (15.8%) and a higher FE for MF (58.0%) compared to the values of Cu (FA: 38.8%, MF: 42.3%), suggesting that Br – may also impede the FF-to-FA process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that Br – was coadsorbed over Cu, and it was previously reported to enhance HMF hydrogenolysis to DMF, we further conducted catalytic tests using BTA­(NTf 2 ) and HBr as the alternative to BTAB (Figure S23). The catalytic results reveal that Cu–Br – delivers a lower FE for FA (15.8%) and a higher FE for MF (58.0%) compared to the values of Cu (FA: 38.8%, MF: 42.3%), suggesting that Br – may also impede the FF-to-FA process.…”
Section: Resultsmentioning
confidence: 99%
“…Since the RDS of the overall process in our work involves a PCET process, it is possible that the addition of the last two hydrogens to FurCH* proceeds via either a PCET or HAT mechanism if they are not the RDS. In addition, there is still a debate on whether the addition of the first hydrogen atom to the oxygen , or carbon in FF’s carbonyl group. Seeking evidence from in situ spectroscopy to understand the reaction pathway should be the focus of future work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through organothiol modification, Chadderdon et al found two competing mechanisms for the reduction of furfural on Cu, where the hydrogenation and hydrogenolysis are produced by ECH, and the coupling product is generated by DER . Choi et al found that halide adsorption promotes electrochemical hydrogenolysis of furfural on Cu, supporting that hydrogenation is only created by ECH, while hydrogenolysis occurs mainly by DER . In contrast, Zou et al prefer hydrogenation on Cu as an ECH process and hydrogenolysis as a mixed DER/ECH process .…”
Section: Introductionmentioning
confidence: 99%